THE ROLE OF THE NEWEST INTERACTIVE DISTANCE TECHNOLOGIES IN FORMATION OF FOREIGN LANGUAGE SOCIOCULTURAL COMPETENCE OF PART-TIME STUDENTS IN TECHNICAL UNIVERSITIES - Ya. S. Gryshchenko; I. A. Sydorenko (Novìtnâ Osvìta, 2014)
The present article is devoted to the determination of the role of the newest interactive distance technologies in the formation of foreign language sociocultural competence of the part-time technical students. At the beginning of the article the quantitative indexes of time intended for the individual work in the form of tutorial via the Internet, classroom tutorial and on-line conferences are presented. The article introduces the detailed review of interactive methods of learning which can be applied during distant teacher-student cooperation at the intersession period. The analysis of means of teacher-student communication through the Internet is also carried out, in frames of which two kinds of communication (on-line and off-line) are considered. To the first category communication by means of the electronic correspondence, exchange of personal points of view at forums, blogging, communication via teacher’s Web page (site) are referred. The latter includes correspondence with the help of ICQ, Quip, Skype and communication through the Webinar system, the notion of which is assiduously studied in our research. The practical part encompasses the results of the experiment conducted with the students of Welding faculty, Faculties of Physical Engineering and Chemical Technology on the platform of Mikogo on the topic “World Famous Inventors and Inventions”. At the final part of the article we made the general conclusion that the Webinar is really an effective tool to form the foreign language sociocultural competence of part-time students in higher technical institutions. As the prospect of our further investigation the following is defined: carrying out the experiments with greater quantity of participants and more detailed revision of possibilities of Webinar platforms employment while foreign language learning.